2002
DOI: 10.3201/eid0808.010474
|View full text |Cite
|
Sign up to set email alerts
|

Serologic Evidence of H1 Swine Influenza Virus Infection in Swine Farm Residents and Employees

Abstract: We evaluated seropositivity to swine and human H1 influenza viruses in 74 swine farm owners, employees, their family members, and veterinarians in rural south-central Wisconsin, compared with 114 urban Milwaukee, Wisconsin, residents. The number of swine farm participants with positive serum hemagglutination-inhibition (HI) antibody titers >40 to swine influenza viruses (17/74) was significantly higher (p<0.001) than the number of seropositive urban control samples (1/114). The geometric mean serum HI antibody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(104 citation statements)
references
References 28 publications
5
93
1
3
Order By: Relevance
“…With regard to other SIV strains other than A(H1N1)pdm09, previous studies found an increased risk of seropositivity to at least one SIV in pig workers, including H1N1,17, 18, 27, 29, 31, 33, 41, 42, 43 H1N218, 28, 31 and H3N228, 29, 30, 44 strains. In our study, we found increased risk of seropositivity both to swine H1N2 and H3N2 Perth.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With regard to other SIV strains other than A(H1N1)pdm09, previous studies found an increased risk of seropositivity to at least one SIV in pig workers, including H1N1,17, 18, 27, 29, 31, 33, 41, 42, 43 H1N218, 28, 31 and H3N228, 29, 30, 44 strains. In our study, we found increased risk of seropositivity both to swine H1N2 and H3N2 Perth.…”
Section: Discussionmentioning
confidence: 98%
“…Pigs are a particularly important species in this regard as the occurrence of both types of SA receptors permits binding of human and avian influenza viruses making them an efficient ‘mixing vessel' 11, 12, 13, 14. Interspecies transmission (in both directions) of swine and human influenza viruses is well recognised, evidenced by the isolation of human influenza virus in swine15, 16 and evidence of swine influenza virus (SIV) infection in people with close occupational17, 18, 19 and/or residential proximity to pigs20, 21; or prolonged exposure at an agricultural fair22. Transmission between pigs and bird species is exemplified by various reports of isolation of SIV from turkeys 23, 24, 25.…”
Section: Introductionmentioning
confidence: 99%
“…Because a relatively small number of zoonotic swine infl uenza virus infection have been documented by virus isolation, whether infections with swine infl uenza viruses are clinically different than infections with routine human infl uenza viruses remains unclear. It is therefore important to pursue virus isolation aggressively when swine farming people show infl uenzalike symptoms [65]. The special environment and lifestyle in southern China provide more chances for wild aquatic birds, domestic poultry, pigs and humans to come in contact closely and hence create an opportunity for interspecies transmission and generation of new reassortant infl uenza viruses.…”
Section: Swine Infl Uenza and Zoonosesmentioning
confidence: 99%
“…A number of studies also demonstrate that zoonotic viruses can be transmitted across the animal-human interface in the context of food animal production ( Table 2). Studies on seroprevalence of H1 swine influenza virus infections 27,70 and hepatitis E 22 indicate that farmers and farm workers can be infected by viruses from food animals. Myers et al reported that swine farmers had higher titers of H1N1 and H1N2 antibodies and greatly elevated risks of seropositivity to these two influenza A viruses (35.3 and 13.8 odds ratios, respectively, as compared with community referents).…”
Section: Evidence For Increased Risks Of Virus Exposure For Farmers Amentioning
confidence: 99%
“…23 Thus, it is not surprising that increased risks of pathogen exposure and infections, both bacterial and viral, have been reported among farmers, their families, and farm workers at poultry and swine operations. [24][25][26][27][28][29][30][31][32][33] …”
Section: Occupational Pathwaysmentioning
confidence: 99%